1985
DOI: 10.2113/gsecongeo.80.5.1379
|View full text |Cite
|
Sign up to set email alerts
|

The importance of CO 2 on freezing point measurements of fluid inclusions; evidence from active geothermal systems and implications for epithermal ore deposition

Abstract: In studies of epithermal precious and base metal ore deposits, estimates of salinity (total dissolved salts) are frequently in error when based on fluid inclusion ice melting measurements in the absence of an independent determination of the CO2 content of the inclusion fluid. For a fluid of known composition, the melting point of ice (Tin) may be calculated from Tm= --• Kimi where Ki is the molal freezing (or melting) point depression constant and mi is the molality of a component i (i = Na +, K +, CI-, CO2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
210
0
11

Year Published

1988
1988
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 430 publications
(232 citation statements)
references
References 16 publications
11
210
0
11
Order By: Relevance
“…It should be noted that equations (7) and (8) implicitly exclude boiling in an open system, and that the homogenization tempera ture is equal to temperature of the solution. Simultaneous cooling and dilution during boil ing in an open system has been discussed by Hedenquist and Henley (1985), and is not treated in this paper.…”
Section: Calculation Methodsmentioning
confidence: 99%
“…It should be noted that equations (7) and (8) implicitly exclude boiling in an open system, and that the homogenization tempera ture is equal to temperature of the solution. Simultaneous cooling and dilution during boil ing in an open system has been discussed by Hedenquist and Henley (1985), and is not treated in this paper.…”
Section: Calculation Methodsmentioning
confidence: 99%
“…The CO 2 liquid and vapour homogenise in these inclusions near 26°C, but the small size precludes accurate determination of homogenisation temperature. Freezing-point depressions in the aqueous inclusions are almost certainly due to dissolved CO 2 (Hedenquist & Henley 1985a). Co-existence of inclusions with widely varying fluid composition suggests that the fluids were immiscible during entrapment Such immiscibility allows estimates of both temperature and pressure to be obtained from fluid-inclusion data.…”
Section: Fluid Inclusionsmentioning
confidence: 99%
“…This relation could represent the immiscibility of an originally aqueous carbonic fluid with consequent gas loss, that is, with CO 2 partitioning to the gas phase. As discussed by Hedenquist and Henley (1985a), the immiscibility and preferential loss of the gas phase to the bubble, in aqueous system with some quantities of CO 2 result in a small decrease of temperature accompanied by a great decrease in the apparent salinities. In this case the boiling trend seems to be strongly masked by the mixing trend.…”
Section: Discussionmentioning
confidence: 98%
“…Hedenquist and Henley (1985a) showed that in most epithermal deposits CO 2 is present as a dissolved gas in fluid inclusions, sometimes in small not visible proportions, and also discussed the effect of these discrete CO 2 concentrations on melting point depression. On the basis of the low-temperature phase relations in the H 2 O-CO 2 system Hedenquist and Henley (1985a) and Diamond (2003),…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation